Orality and Writing: fields of research in pedagogy of the Mother Tongue - Quitián Bernal, Sandra Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents the analysis carried out in the research line “Discursive Activities of Orality and Writing, within the framework of the study” State of Art of Research in the Master in Pedagogy of the Mother Language. The result of this documental study, with qualitative characteristics, allows to reveal the correct answers of the research as well as the identification of signs that bring us to consider the Information and Communication Technologies as an emergent condition and so with the need to be consider in the formulation of the line, particularly from its relation with teaching process and orality and writing learning, in the Master in Pedagogy of the Mother Language.